Overcooling Effect on Content of LPO Transit Products and SOD Activity in Yellow Mealworm Tenebrio molitor - Gulevskiy, A. K.; Grischenkova, E. A.; Relina, L. I.; Kareva, L. V. (Problems of Cryobiology and Cryomedicine, 2006)
Overcooling influence on transit products of lipid peroxidation (LPO) and superoxide dismutase (SOD) activity in yellow mealworm Tenebrio molitor has been investigated. It has been shown that cold-tolerant and cold resistant ontogenetic stages differ by LPO intensity and SOD activity parameters. Preliminary cold acclimation at moderately low temperatures affects diene conjugate and ketodiene accumulation and enzyme activity. The obtained results testify to the fact that cold-tolerant 8-10 instar larvae are able of maintaining a constant level of redox processes after overcooling unlike sensitive to low temperatures 3-5 instar larvae. Metabolic protective program preventing disorders of pro-oxidant and anti-oxidant balance and progress of oxidative stress is likely to â€œswitch onâ€ during cold acclimation which may play a significant role in biochemical mechanisms of cold tolerance in insects.